Pengaruh Kepemimpinan Demokratis Kepala Sekolah Terhadap Kinerja Guru dan Pegawai pada SMP Negeri 3 Pamboang - Muhammad Nadir (Fakultas Keguruan dan Ilmu Pendidikan Univ. Al Asyariah Mandar Sulbar, 2017)
Leadership of principals in order to improve the performance of teachers and employees is very important, it is fitting discipline applied to every school, both government and private. A performance of good teachers and employees is a step towards achieving the goals of a school so that productivity is a determinant in achieving school goals. This study aims to determine the influence of principal leadership on the performance of teachers and employees of SMP Negeri 3 Pamboang. The research design used is quantitative research. The sample of research is 35 employees of SMP Negeri 3 Pamboang and data collection in the form of questionnaire method, interview, observation. While for data processing is analyzed for Validity and Realibility test using Alpha Cronbach formula using computer program. The analysis technique used is simple regression analysis. Based on the results of data calculations and analysis used, obtained the regression equation, Y  20,091 0,441X. Results Hypothesis test t shows t count = 4.86 and t table = 2.032 with the value of significance = 0,000